2013
DOI: 10.1172/jci68182
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent hepatic lymphoid organization directs successful immunity to hepatitis B

Abstract: Hepatitis B virus (HBV) is a major human pathogen that causes immune-mediated hepatitis. Successful immunity to HBV is age dependent: viral clearance occurs in most adults, whereas neonates and young children usually develop chronic infection. Using a mouse model of HBV infection, we sought mechanisms underpinning the age-dependent outcome of HBV and demonstrated that hepatic macrophages facilitate lymphoid organization and immune priming within the adult liver and promote successful immunity. In contrast, lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 42 publications
(51 reference statements)
1
79
0
Order By: Relevance
“…CXCL13 fused with green fluorescent protein (GFP) was found to enhance the level of GFP antibody detected and to elicit higher levels of specific IgG1 antibodies than of IgG2a antibodies, which indicates a Th2 response and a contribution factor to humoral immunity (37). Recent studies have also shown that CXCL13 recruits B cells to nonlymphoid organs, contributing to the organization of local immune responses against influenza and hepatitis B virus infections (53,54). In our present study, CXCL13 was inserted into the genome of the RABV and expressed in a considerable quantity both in vitro and in vivo, which was shown to have strong biological activity in a transwell model and to help recruit the cells expressing CXCR5 to the injection sites in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL13 fused with green fluorescent protein (GFP) was found to enhance the level of GFP antibody detected and to elicit higher levels of specific IgG1 antibodies than of IgG2a antibodies, which indicates a Th2 response and a contribution factor to humoral immunity (37). Recent studies have also shown that CXCL13 recruits B cells to nonlymphoid organs, contributing to the organization of local immune responses against influenza and hepatitis B virus infections (53,54). In our present study, CXCL13 was inserted into the genome of the RABV and expressed in a considerable quantity both in vitro and in vivo, which was shown to have strong biological activity in a transwell model and to help recruit the cells expressing CXCR5 to the injection sites in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In a transgenic mouse model, Publicover et al demonstrated that KCs in 8-to 12-wk-old C57BL/6 mice facilitated lymphoid organization and immune priming and promoted successful immunity against HBV. In contrast, lymphoid organization and immune priming was substantially diminished in 3-to 4-wk-old and KC-depleted 8-to 12-wk-old C57BL/6 mice, leading to abrogated HBV immunity (31). Therefore, it is reasonable to speculate that changing gut microbiota profiles at various stages of gut development provides signals that affect the outcomes of immune activation in the liver and determines the transition from HBV tolerance to clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, whilst CXCL13 and macrophages facilitate lymphoid organization and successful HBV immunity of the adult, the young mice have abrogated HBV immunity due to greatly diminished CXCL13/macrophage-mediated immune priming [7]. Nonetheless, neonatal immune system is not intrinsically defective and enhanced TLR responses of the neonatal DCs as compared with the adult have been reported [8,9].…”
Section: Hepatitis B Virus (Hbv) Is Known To Cause Age-dependent Infementioning
confidence: 99%